Reforming beyond Yoda's principle - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
“Teachers must learn, unlearn and relearn” — NST, Aug 10) to bring up the discourse on why teachers need to learn to accept that things have changed around us, and that there is an urgent need to unlearn some of the ‘old’ ways. At the same time, to relearn how to adapt to the changes ahead. to acknowledge that it is not only confined to the teachers but also to all learners, which cuts across the entire community globally. They, too, need to learn of the rapid changes taking place if education is to be fully supported for future learning, notably from the dimensions of policy- and decision-making and implementation. Thus leading to the unlearning and relearning of various policy dimensions as well to suit the changing times.